Transformasi Pembelajaran Bahasa Indonesia Berdiferensiasi di Sekolah Dasar melalui Pendekatan Teaching At The Right Level (TaRL) - Latif, Azminudin; Markhamah, Markhamah; Rahmawati, Laili Etika (Jayapangus Press, 2025)
Differentiated Indonesian language instruction plays a vital role in supporting the optimal achievement of literacy competencies among elementary school students. This study aims to describe the implementation, identify obstacles, and explore solutions in applying differentiated Indonesian language instruction through the Teaching at the Right Level (TaRL) approach at SD Negeri 03 Tunggulrejo. The research was conducted with fourth-grade students who exhibited diverse levels of learning abilities. The method used was a descriptive qualitative approach to comprehensively illustrate the strategies, challenges, and solutions encountered during the implementation of TaRL. Data collection techniques included classroom observation, in-depth interviews with teachers and students, as well as documentation of instructional materials. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, with validity tested through triangulation and member checking.The main findings of the study indicate that the TaRL approach is effective in grouping students based on initial assessment results and in designing instruction tailored to their individual needs. Students with lower proficiency levels showed gradual improvement in reading and writing comprehension, while higher-level students were appropriately challenged. The challenges encountered included limited time, a lack of varied learning media, and the need for teacher adaptation to the new approach. However, through well-planned differentiated instruction strategies, teacher training, and collaboration among teachers, parents, and students, the implementation of TaRL was more effective. This study concludes that integrating the TaRL approach into differentiated Indonesian language instruction not only enhances students' literacy skills but also fosters learning motivation and creates a more inclusive, adaptive, and meaningful learning experience for all students.